Accounting for actions and omissions: a discourse analysis of student nurse accounts of responding to instances of poor care. (15th January 2016) - Ion, Robin; Smith, Kate; Moir, Jim; Nimmo, Sheila
Abstract: Aims: To explore how nursing students account for decisions to report or not report poor care witnessed on placement and to examine the implications of findings for educators. Background: Concern has been raised about the extent to which cases of poor care go unreported. Failure to report cases may have serious consequences for patient safety. Design: Semistructured interviews were conducted with 13 undergraduate students at a UK university during 2013. They were asked to consider their response to episodes of poor practice witnessed on placement. Methods: Data were transcribed verbatim and categorized according to whether or not students reported concerns. Cases were analysed in accordance with Potter and Wetherall's version of discourse analysis to identify the discursive strategies used to account for decisions to report or not report poor practice. Results: Participants took care to present themselves in a positive light regardless of whether or not they had reported an episode of concern. Those who had reported tended to attribute their actions to internal factors such as moral strength and a commitment to a professional code. Those who had not or would not report concerns provided accounts which referred to external influences that prevented them from doing so or made reporting pointless. Conclusion: This study provides information about how students account for their actions and omissions in relation to the reporting of poor care. Findings suggest ways educators might increase reporting of concerns.